Virtual laboratory based online learning: Improving environmental literacy in high school students - Anggi Angreani; S. Saefudin; Rini Solihat (University of Muhammadiyah Malang, 2022)
Oftentimes the increase in industrial development is the cause of environmental problems. Environmental problems can be overcome by the presence of humans who care about the environment or have environmental literacy skills. Environmental literacy skills can be instilled from an early age, for example through practicum learning in schools. However, considering that the Covid-19 pandemic is one of the obstacles in carrying out the practice, virtual laboratory-based online learning is carried out. This study was aimed to improve students' environmental literacy through virtual laboratory-based online learning that has been developed. This research is quasi experiment with pre-test and post-test research design Control Group Design. The total sample of the study was 70 students of class X at state senior high school. The research instrument used was in the form of test questions about environmental changes material and environmental literacy questionnaires. The results showed that the N-gain value of environmental literacy in the experimental class was 29% high, 60% moderate, 11.42% low with the percentage of attitudes 66.62% and 63.43% behavior. Meanwhile, for the control class, the N-gain value was 9% high, 48.57% moderate, 42.85% low and 68% attitude and 67% behavior. This shows that virtual laboratory-based online learning contributes to increasing environmental literacy skills.